Pabrikasi Membrane Electrode Assembly Menggunakan Metode Decal Transfer Dengan Katalis Platina Didukung Karbon Dan Variasi Ketebalan - Adnyana, Pande Nyoman Agus; Joni, I Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract The use of conventional vehicles increases dependence on fossil fuel energy whose resources are increasingly depleted, not to mention the problems caused by emission gases. Hydrogen is an alternative energy that can be a solution by utilizing fuel cell technology in electric-based vehicles. Proton exchange membrane fuel cell (PEMFC) is one type of fuel cell technology that is commonly applied to electric vehicles. However, there are several obstacles, such as performance and cost effectiveness, so further development is needed. The main component of PEMFC is the membrane electrode assembly (MEA) which is where the electrochemical reaction occurs. The purpose of this study is to analyze the effect of MEA thickness on its performance which is tested by PEMFC testing. In this study, MEA was fabricated using the decal transfer method with variations in MEA thickness, namely 140 ?m, 170 ?m, and 200 ?m. Based on the results of PEMFC testing, the MEA sample with a thickness of 140 ?m showed the best results with the highest voltage value produced, namely 9800 ?V in conditions without resistance. At a certain resistance, the highest current density and maximum power density values produced are 9.1 ?A/cm2 and 12204 ?W/cm2. Keywords: Decal Transfer, Membrane Electrode Assembly, MEA Thickness